Variation in the snow cover on the Qilian Mountains and its causes in the early 21st century. Issue 6 (1st November 2016) - Jiang, Youyan; Ming, Jing; Ma, Pengli; Wang, Pengling; Du, Zhencai
ABSTRACT: Based on MODIS data, we analyzed the spatial distribution and the intra- and inter-annual variations of the snow cover in the Qilian Mountains. In addition to discussing regional climate, we discussed the reasons for the snow cover pattern variations. The spatial distribution of the snow cover in the Qilian Mountains is uneven, and the snow cover in the west is significantly greater than that in the east. The difference in the intra-annual variations of the snow cover at different altitudes is large, and the general seasonal cycle exhibits two maxima and one minimum. The snow cover and precipitation in the Qilian Mountains were consistently increasing from 2000 to 2005, but they generally decreased from 2008 to 2013. The influences of temperature, wind speeds and precipitations on snow cover variation at different altitudes vary greatly, with the snow cover being more sensitive to precipitation in the winter, while temperature and precipitation are the major factors that affect the snow cover in the spring.